Can Carbon Emission Regulation Achieve a Dual Target of Low Carbon and Employment? An Empirical Analysis Based on China’s Provincial Panel Data - Shang, Lin; Xu, Pingxiang (Frontiers in Energy Research, 2022)
The Phillips curve of environment (EPC) and the environmental Kuznets curve of employment (EKCE) both indicate that the low-carbon economic transition can promote employment growth. Based on Chinese provincial dynamic panel data from 2005 to 2019, the GMM method is used to evaluate these two hypotheses. The results show that there is a remarkable U-shaped relationship between carbon emission regulation and employment, which means the EKCE is better than EPC to match the situation in China. So, a dual target of low carbon and employment can be achieved with the strengthening of environmental regulations. However, because of the difference in economic development, industrial structure, human capital, economic openness, wage of employees, and marketization, the significance level of the relationship between them varies substantially across regions. For the eastern and central regions, it can be characterized by EKCE, and for the western region, the EPC is more significant. Therefore, in order to realize the double dividend more effectively, it is necessary to accelerate the market-oriented reform of carbon emission while implementing differentiated carbon regulation policies and promoting the synergistic effect of administrative intervention mechanism and market mechanism.